Rational Application of Fertilizer Nitrogen to Soil in Combination With Foliar Zn Spraying Improved Zn Nutritional Quality of Wheat Grains - Xia, Haiyong; Xue, Yanfang; Liu, Dunyi; Kong, Weilin; Xue, Yanhui; Tang, Yanyan; Li, Jin; Li, Dong; Mei, Peipei (Frontiers in Plant Science, 2018)
To alleviate human zinc (Zn) deficiency, it is worthy to develop rational agronomic managements to achieve high yielding and high resource-use efficiency wheat (Triticum aestivum L.) grains biofortified with Zn. Effects of application of three rates of nitrogen (N) fertilizer (75, 200 and 275 kg·ha–1) to soil in combination with three foliar applications (deionized water, Zn alone, and a combination of Zn and sucrose) on grain yield, yield components, grain Zn concentration, protein, phytic acid (PA), phosphorus (P), calcium (Ca), and carbon (C), as well as on Zn bioavailability, were investigated in four wheat cultivars (‘Jinan 17’, ‘Jimai 20’, ‘Jimai 22’ and ‘Luyuan 502’) under field conditions. Enhanced N increased Zn and protein concentrations as well as bioavailability; excessive N input did not result in further improvements. Zinc spraying was more effective than soil fertilizer N application, the spray of Zn (with or without sucrose) increased grain Zn concentrations by 11.1–15.6 mg·kg–1 (27.1%–38.1%), and increased grain Zn bioavailability, estimated using total daily absorbed Zn (TAZ) and molar ratios of PA/Zn) and PA  Ca/Zn, by 0.4–0.6 mg d–1 (28.6–42.9%), 23.1%–27.4% and 24.0%–28.0%, respectively. Remarkably, increases caused by ‘Zn + sucrose’ were higher than spraying Zn alone. Grain Zn bioavailability was more sensitive to the selection of cultivar than Zn concentrations. Among cultivars, the higher the grain yields and concentrations of antinutritional compounds, the lower the grain Zn nutritional quality would be. 200 kg N ha–1 application rate in combination with foliar spraying of ‘Zn + sucrose’ maximized grain Zn concentrations of ‘Jinan 17’, ‘Jimai 20’, ‘Jimai 22’ and ‘Luyuan 502’ to be 59.4, 56.9, 55.8 and 60.9 mg kg–1, respectively, achieving the target value for biofortification. Additionally, PA/Zn and PA  Ca/Zn of ‘Jinan 17’, ‘Jimai 20’ and ‘Luyuan 502’ were less than 15 and 200, and TAZ was maximized to be 2.2, 2.0 and 2.1 mg d–1, respectively, indicating higher bioavailability. Therefore, optimal soil N and foliar Zn management together with suitable cultivars maintained high grain yield with lower N input and could substantially increase grain Zn nutritional quality simultaneously.